ĐÁNH GIÁ KHẢ NĂNG CHỊU ĐỰNG CÁC YẾU TỐ LAO ĐỘNG BAY CỦA HỌC VIÊN PHI CÔNG QUÂN SỰ VIỆT NAM VÀ LIÊN BANG NGA - A. A., Blaginin; I. I., Zhiltsova; Đặng, Quốc Huy; Lê, Văn Hướng; Yu. A., Emelyanov; N. V., Alzhev (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
ASSESSMENT OF THE TOLERANCE TO THE OCCUPATIONAL FACTORS OF FLYING LABOR OF VIETNAMESE MILITARY PILOT OF THE SOCIALIST REPUBLIC OF VIETNAM AND THE RUSSIAThe article studies the characteristics of tolerance to the occupational factors of flying labor in military pilots (MP) of the Socialist Republic of Vietnam with the aim of fulfill the psychophysiological training system for military pilots. The study involved 17 Vietnamese and 24 Russian MP between the ages of 19 and 22. Conducted an endurance assessment against flight factors such as overload, hypoxia and effects of balance dynamics on the basis of using statoergometric, hypoxia test and vestibular organ test “OR-10”. Before and after being subjected to the above effects, MP were evaluated for psychophysiological characteristics by measuring critical flicker fusion frequency (CFFF) and reaction time test (RTT) and physiological indicators about computer balance ability during hypoxia. In addition, height and weight indexes were also included in the study.The results showed that there was a significant difference between the two study groups with the difference in height, weight, BMI and flying overload capacity in the Russian MP group were higher. At the same time, there was also a difference in psychophysiological indicators between the two groups. Assessment of hypoxia tolerance and cochlear vestibular testing (OR-10) based on computerized balance indices showed different predispositions for each group. This is because in the Vietnamese MP group, there has appeared an adaptive mechanism in a state of greater exertion than in the Russian group.The results of the study show that it is necessary to improve the psychophysiological training system for Vietnamese pilots in order to improve their ability to resist the effects of occupational factors during flight operations highly maneuverable aircraft manufactured by the Russian Federation.